Multigene signatures for early breast cancer in clinical practice: A report of the Lombardy genomic assays for breast cancer working group - Licata, Luca; Cosentini, Deborah; De Sanctis, Rita; Iorfida, Monica; Caremoli, Elena Rota; Vingiani, Andrea; Simoncini, Edda Lucia; Pruneri, Giancarlo; Munzone, Elisabetta; Bianchini, Giampaolo; Zambelli, Alberto; Tondini, Carlo (Frontiers in Oncology, 2023)
The increasing understanding of breast cancer biology has provided the basis for the development of multigene signatures aimed to improve the capability of clinicians to assess patients’ prognostication and risk stratification. Incorporating these tools in clinical practice has profoundly impacted on the decision-making process for the adjuvant therapy of patients with ER+/HER2- early breast cancer and the results from prospective adjuvant trials have strengthened the clinical utility of multigene signatures in this setting. In July 2019, Lombardy was the first Region in Italy to reimburse genomic testing for patients with ER+/HER2- early breast cancer. Three years later, a group of investigators from six referral Cancer Centers in Lombardy convened to debate the use of multigene signatures in clinical practice and share their own experience with the tests after reimbursement. Here, we reviewed relevant data on the role of multigene signatures in tailoring adjuvant chemotherapy for patients with ER+/HER2- early breast cancer and discussed about the optimal use of these assays in current clinical practice. As the treatment landscape of early breast cancer evolves and novel questions about the possible additional applications of multigene assays arise, we also provide our viewpoint on the potential implementation of the assays in the evolving scenario of ER+/HER2- early breast cancer treatment.